2022
DOI: 10.1021/acs.jafc.2c04337
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Prevents against Ethanol-Induced Liver Injury by Mitigating Ferroptosis via Targeting Brain and Muscle ARNT-like 1 in Mice Liver and HepG2 Cells

Abstract: The circadian clock acts a pivotal part in human daily physiology and metabolism. Excess alcohol consumption disturbs the circadian rhythm of several metabolism-related genes of the liver. Melatonin is a member of the foremost hormones secreted by the pineal gland with numerous pharmacological properties in quite a number of diseases. However, its potential roles and possible mechanisms in ethanol-induced ferroptosis are still not clear completely. Ethanol feeding studies were performed upon a chronic-plus-bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Activated Nrf2 promoted expression levels of FTH1, FTL1, GPX4, and SLC7A11, thus balancing iron level, reducing oxidative stress, preventing lipid damage, ultimately inhibiting ferroptosis ( Wang et al, 2022a ). Nrf2 also controlled iron transport through TFR1 and FPN1, and mitigated lipid peroxidation by modulating expression levels of ACSL4 and PTGS2 ( Zhao et al, 2022 ). Growing evidence suggested that heavy metals might influence ferroptosis through Nrf2 signaling pathway ( Liu et al, 2022b ; Ouyang et al, 2023 ; Lan et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…Activated Nrf2 promoted expression levels of FTH1, FTL1, GPX4, and SLC7A11, thus balancing iron level, reducing oxidative stress, preventing lipid damage, ultimately inhibiting ferroptosis ( Wang et al, 2022a ). Nrf2 also controlled iron transport through TFR1 and FPN1, and mitigated lipid peroxidation by modulating expression levels of ACSL4 and PTGS2 ( Zhao et al, 2022 ). Growing evidence suggested that heavy metals might influence ferroptosis through Nrf2 signaling pathway ( Liu et al, 2022b ; Ouyang et al, 2023 ; Lan et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cells were fasted for 12 hours before the treatment. To induce ALD-like injury to HepG2 cells, they were treated with a concentration of 200 mmol/L ethanol for 24 hours as previously reported 26,27 . Following this, cells were cotreated with various levels of drugs (1.875 to 5 μ mol/L) as well as 200 mmol/L ethanol for 24 hours.…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%
“…Ischemic stroke is a life‐threatening condition that claims millions of lives worldwide each year 1 . In China, stroke has become the number one killer, causing millions of deaths annually.…”
Section: Introductionmentioning
confidence: 99%